Gaps in Participation in Unpaid Care Work: The Case of Colombia - Atis Ortega, Karen Liseth; Fajardo Hoyos, Claudia Liceth; González Hoyos, Yuliana Karolina (Sociedad y Economía, 2025)
IntroductionIn Colombia, wide gender gaps persist in the distribu- tion of time, although evidence at the departmental le- vel remains limited.ObjectiveThis article conducts a subnational analysis, estimating gender differences in participation in unpaid care work (UCW) across departments and identifying the demo- graphic, educational, and household factors associated with such participation.MethodologyUsing microdata from the 2022 GEIH (Other Forms of Work module), probabilistic models with departmental fixed effects, interactions, and controls for age, mi- gration, education, marital status, ethnic self-identifi- cation, and household characteristics were estimated. Predicted probabilities and marginal effects are presen- ted.ResultsFindings show that 92% of women engage in UCW ac- tivities, compared to 64% of men. The model confirms higher female participation probabilities in all depart- ments, with particularly wide gaps in San Andrés and Providencia (~50 percentage points) and significant differences in Cesar, Sucre, and Bolívar. These dispari- ties tend to narrow with higher educational levels but remain large among Afro-descendant and Indigenous populations, as well as among individuals with a migra- tory condition.ConclusionsUCW disproportionately falls on women, with marked territorial heterogeneity. Therefore, care policies must adopt territorial, gender, and intercultural approaches, aligned with the National Care System and accompa- nied by strategies of shared responsibility, service pro- vision, and the right to time, in order to reduce these gaps and expand opportunities for well-being.